The role of contractile reserve by stress test echocardiography for predicting cardiac resynchronization therapy responder: systematic review and meta-analysis - Lefi, Achmad; Dewi, Ivana Purnama; Dewi, Kristin Purnama; Mulia, Eka Prasetya Budi; Subagjo, Agus; Dharmadjati, Budi (Open Access Macedonian Journal of Medical Sciences, 2021)
Introduction: Up to one-third of patients who received resynchronization devices do not experience full benefit of cardiac resynchronization therapy (CRT). Echocardiography plays an important role in heart failure patients treated with CRT. Contractile reserved is a strong prognostic factor to predict positive response to CRT (CRT responder). Objective: We perform a systematic review and meta-analysis of published data to assess the relationship between contractile reserve (CR) and response to CRT. Methods: We conduct a systematic search from major medical databases on all clinical trials published up to June 2020, written in English, full-text availability, and human subject. We used Newcastle-Ottawa Scale to measure the quality of evidence. We employed the Mantel–Haenszel random-effects meta-analysis of using RevMan 5.4. Results: We identified 17 studies involving 1399 patients. The type of stress was either dobutamine (n=15) or exercise (n=2). The presence of CR was associated with a higher chance of CRT responder (OR 7.68, 95%CI 4.27–13.82, p<0.001) using a random-effects model. The ORs slightly differed when studies were analyzed separately based on the stress test type and definition of CR. Contractile reserve, assessed with dobutamine stress echocardiography (DSE), defined as an increase in LVEF (OR 5.10, 95% CI 2.29–11.32, P <0.00001) was numerically lower than defined as increased LV contractility (OR 6.86, 95% CI 3.36–12.88, P <0.00001). The presence of CR assessed with exercise stress test are associated with higher chance of CRT responder (OR 49.11, 95% CI 15.04–160.36, P <0.00001). From our meta-analysis, we found non-ischemic has better respond to CRT compare to patient with ischemic etiology (OR 0.41; 95% CI 0.31-0.55, P <0.01). Conclusion: The presence of CR during stress test echocardiography with either dobutamine or exercise stress test is associated with a higher chance of CRT responder.